An Overview of Wasting and Stunting based on Nutritional Status Assessment for Toddlers (INCH : Journal of Infant and Child Healthcare, 2023)
Malnutrition of toddlers is the main problem causing growth and development disorders of toddlers today. This problem causes children to experience stunting. The need to detect the nutritional status of toddlers as an effort to manage stunting from an early age. This study aims to identify toddlers with malnutrition and stunting in Parit Baru Village, Kampar. Descriptive research method with Total Sampling technique to get 152 children under five. Data collection was carried out by measuring body weight and height. Data is written in the Observation Sheet. The results showed that the nutritional status of toddlers based on weight/age was in the underweight category of 8.5%, based on height/age it was in the short/stunting category of 5.9% and based on weight/height it was in the wasting category of 4, 6%. The conclusion is that most toddlers have good nutritional status but there are still toddlers with malnutrition